The Use of Personalized Health Reports in a Student-Run Free Clinic - Darian, Talin; Ma, Pei Chan; Su, Lydia; Mendez, Jennifer (Journal of Student-Run Clinics, 2020)
My Health Report (MHR) is a computer program that prints out personalized health reports for patients based on their basic health data and laboratory test results. Reports are available in four languages. The goal of MHR is to improve health communication and education. This program has been used by medical students in a student-run free clinic in Madison Heights, Michigan, since 2011 and supports students’ efforts in providing patient-centered communication and education materials to an underserved population across multiple languages. Given its simplicity and portability, MHR may add value to student-run clinics elsewhere.